Realitas Pelayanan Sosial Pemerintah Kabupaten Bantul Sebagai Usaha Meningkatkan Kesejahteraan Lansia Terlantar (Studi Implementasi Pelayanan Sosial Lansia Terlantar di Kelurahan Tirtomulyo, Kretek, Bantul) - , SIBBIL RUSDIANA ADDRIYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nowadays, the life expectancy rate in Indonesia is increasing and affect the growing number of elderly. Dilemma canât be avoided, it is a great achievement for the government but also raise a number dependency. Elderly will be a new problems if not handled properly. Conditions of many poor people lead to the risk of the emergence of abandoned elderly. Welfare is the right of all people nor with the elderly. Social services elderly is one of the things done by the government for the welfare of the elderly are abandoned. Various programs is given to the elderly, both in the form of money, food and services. Bantul government is one of the parties concerned with the welfare of the elderly began then formulated a policy to provide social services to the elderly independently in Bantul. Number of elderly in Bantul is at second place in the province after Gunungkidul. Abandoned elderly social services provided to the elderly who have not received any assistance from both central and local government. Existing programs in Bantul for social services elderly is ASLUT, homecare, and Empowerment of the Elderly. This study wanted to see the reality of the implementation of social services elderly in 2013 from the Department of Social Bantul given to the elderly in the Kelurahan Tirtomulyo. Merilee S. Grindle implementation theory which has two major variables, namely the contents of the policy and implementation environment is used as a reference for the research underlying this. The research method used is descriptive qualitative method of analysis in order to find a more in-depth answer. Retrieval techniques with purposive sampling of informants is reinforced by snowball sampling. Informants were interviewed informants are 17 people with 13 people purposive sampling results and snowball sampling results of 4 people. Informants of this study consisted of Bantul Social Service, three receivers of ASLUT, two elderly empowerment receivers, one Homecare receiver, three people from the Kelurahan as well as a Tirtomulyo ASLUT companion, Soropadan hamlet, Karen Kader and Kergan. Informant of snowball sampling results are Kecamatan of Kretek, PSTW Budhi Dharma, TKSK Kretek, and Social Service DIY. Method of collecting information through observation, documentation and media interviews directly. The results on the field is well-triangulated by existing observations and documentation can be found so that the results are valid. The location chosen for the study is Kelurahan Tirtomulyo, Kretek because in 2013 only a third region that receives the service program. Kelurahan Tirtomulyo included in predominantly rural areas are farmers. Almost all of the village is surrounded by green rice field. This shows that there is in the region of the elderly who were formerly employed as a farmer that has no severance pay or retirement benefits that formal. The reality on the field shows some fundamental things that are difficult to see changes in the lives of Tirtomulyo elderly. There are some elderly people who do not get the program and Empowerment Elderly homecare program. So it is difficult to assess the well-being of elderly in the Kelurahan Tirtomulyo based social service programs Bantul elderly. Only the distribution ASLUT running on target. In addition to the existing data in the elderly empowerment list shows that they have a pretty good economy so it canât be said to be displaced. Lack of communication between stakeholders influencing the implementation of this program. in addition, there are data collection abandoned elderly were less precise so there needs to be more attention in data collection. The formulation of the program needs to be balanced with a mature strategy so as not to complicate the implementation in the field. Programs are more effective when given continuous nature. In addition to the communication between the stakeholders that need to be improved, monitoring and evaluation of programs need to be implemented to the maximum in order to give an overview of implementation in the field and input for the future.